A lightweight multi‐beam cylindrical Luneberg lens antenna loaded with multiple dielectric posts. Issue 1 (29th October 2018) - Liu, Kunning; Yang, Shiwen; Jiang, Qiufang; Qu, Shi‐Wei
Abstract: A multi‐beam cylindrical Luneberg lens antenna loaded with multiple light dielectric posts for the purpose of light weight is presented. The antenna is based on a parallel‐plate waveguide and specifically composed of 10 E‐shaped patch antennas feeds, 2 parallel plates, and 491 epoxy posts. The equivalent gradient index of the Luneberg lens antenna is realized via the positions of the epoxy posts between the parallel plates. The features of low‐profile height (0.55 λ ) and large radiating area (4.4 × 0.55 λ 2 ) of the cylindrical Luneberg lens result in wide beamwidth in elevation plane and high gain while operating at 4 GHz. Consequently, the 3 dB beamwidth in the elevation plane is >65°. Furthermore, the multi‐beams cover a wide scan angle of 120° in the azimuth plane. The measured aperture efficiency of the fabricated lens antenna is above 50% from 3.9 to 4.3 GHz. In addition to the good radiation performance, features of light weight and ease of fabrication have also been demonstrated for the proposed lens antenna.